The description of a new marmoset genus, Callibella (Callitrichinae, Primates), including its molecular phylogenetic status - van Roosmalen, Marc G.M.; van Roosmalen, Tomas (Neotropical Primates, 2003)
This paper describes a new genus of Amazonian marmosets, the dwarf marmoset Callibella, formerly identified as Callithrix humilis (Van Roosmalen et al., 1998), and reports its phylogenetic relationship to other callitrichines, based on 902 base pairs (bp) of the mitochondrial control region DNA sequence. The molecular data indicate an early divergence of Callibella humilis, prior to the divergence of Cebuella pygmaea from the ancestral Amazonian marmoset stock. The high degree of divergence of this new taxon warrants its placement in a distinct genus, Callibella. New observations from the morphology, physiology, ecology, and ethology of the dwarf marmoset are presented which support this classification.